AGRESI ISRAEL TERHADAP PALESTINA PERSPEKTIF HUKUM HUMANITER INTERNASIONAL - Yuliantiningsih, Aryuni (Faculty of Law, Universitas Jenderal Soedirman, 2009)
Israel’s agrresion to Palestina has international reactions because of enormous victims caused by that action, whom mostly were civilians. According humanitarian law, Israel’s agression to Palestina had breached humanitarian law principles, there are : humanity principle, limitation principle and distinction principle. Israel has done war crimes so international society asked how Israel can be justiced ? There are three mechanism to enforce humanitarian law. First, the contracting parties of Jeneva Convention State to enact any legislation neccessary to provide effective penal sanction for person committing or ordering to be comitted any of the grave breaches , second by ad hoc tribunal and third by International Criminal Court, but it is rather difficult to prosecute Israel because Israel don’t ratificate Roma Statuta 1998. Kata kunci : Agresi Israel, Palestina